2016
DOI: 10.18052/www.scipress.com/ijet.8.32
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heat Treatment on the Mechanical Properties of SAE 1035 Steel

Abstract: Abstract. The effect of various heat treatment operations (annealing, normalizing, tempering) on mechanical properties of 0.35% carbon steel was investigated. The change in the value of endurance limit of the material as a result of the various heat-treatment operations were studied thoroughly. It was found that the specimens tempered at low temperature (200 0 C) exhibited the best fatigue strength. Microscope was used to characterize the structural properties resulting from different heat treatment processes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In contrast, the uniform steel specimen microstructure includes finer grains relative to the structure of annealed steel. Obiukwu Osita, et al [11] They investigated the influence of various heat treatment procedures on mechanical properties of 0.35% carbon steel (annealing, normalizing, tempering). The results of the tests of tensile, impact and hardness revealed that the mechanical properties differ with each condition of heat treatment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, the uniform steel specimen microstructure includes finer grains relative to the structure of annealed steel. Obiukwu Osita, et al [11] They investigated the influence of various heat treatment procedures on mechanical properties of 0.35% carbon steel (annealing, normalizing, tempering). The results of the tests of tensile, impact and hardness revealed that the mechanical properties differ with each condition of heat treatment.…”
Section: Literature Reviewmentioning
confidence: 99%